Mathematical Concept Understanding: the Impact of Integrated Learning Model - Asfar, A.M.Irfan Taufan; Asmawaty, Asmawaty; Asfar, A. M. Irfan Akbar; Nursyam, Aisyah (Universitas Islam Raden Intan Lampung, INDONESIA, 2019)
This study aims to investigate the improvement of students' mathematical concepts understanding through the application of Guided, Explained, Collaborated and Evoked (GECE) Learning Strategy. The GECE Learning Strategy originates from the integration of the Auditory Intellectually Repetition (AIR) learning model and Guided Discovery learning model. The quasi-experimental with nonequivalent control group design was employed in this study. The instruments used were a test in the form of a description based on real-world concepts and a questionnaire to determine students' responses in the process of learning mathematics. Based on the results of hypothesis testing using the Mann-Whitney test, it was obtained that p kurang dari α (0.001 kurang dari 0.005) which shows that the application of the GECE learning model affects students' mathematical concept understanding with n-gain of 0.62 (medium category). The effectiveness of the learning model applied was measured using Cohen's formula and a value of 1.88 (high category) was obtained. The results were also supported by positive students' responses of 3.45 which means that the integration of the Auditory Intellectually Repetition (AIR) learning model and Guided Discovery learning model could effectively improve students' mathematical concepts understanding.